2022
DOI: 10.3390/ijms231810973
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Mechanism of Pre-mRNA Splicing of Tiny Introns from the Genome of a Giant Ciliate Stentor coeruleus

Abstract: Stentor coeruleus is a ciliate known for its regenerative ability. Recent genome sequencing reveals that its spliceosomal introns are exceptionally small. We wondered whether the multimegadalton spliceosome has any unique characteristics for removal of the tiny introns. First, we analyzed intron features and identified spliceosomal RNA/protein components. We found that all snRNAs are present, whereas many proteins are conserved but slightly reduced in size. Some regulators, such as Serine/Arginine-rich protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The nucleomorph genome is another example of extreme genome reduction in an intracellular symbiosis and, like those of mikrocytids, its introns are not only short, but also fall into a narrow size range: 18 to 21 bp in this case. The smaller and more narrowly constrained introns of mikrocytids are matched only by the 15–16 bp introns of heterotrich ciliates [ 53 , 54 ], which, seemingly against the trend, are free-living organisms with very large cells, nuclei, and genomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nucleomorph genome is another example of extreme genome reduction in an intracellular symbiosis and, like those of mikrocytids, its introns are not only short, but also fall into a narrow size range: 18 to 21 bp in this case. The smaller and more narrowly constrained introns of mikrocytids are matched only by the 15–16 bp introns of heterotrich ciliates [ 53 , 54 ], which, seemingly against the trend, are free-living organisms with very large cells, nuclei, and genomes.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, like other non-coding sequences, introns in endosymbionts might simply gradually shrink in size due to genome erosion, where reduced DNA repair mechanisms lead to a bias for deletions over insertions. This could presumably continue until a functional threshold is hit, below which the introns might be too short to be efficiently spliced and further gradual reductions would be strongly deleterious [ 54 ]. This threshold could be slightly different in systems evolving independently, for instance because introns in organisms with lower intron densities and reduced spliceosomes also tend to evolve greater dependence on sequence conservation for spliceosomal recognition and base-pairing with the snRNAs [ 56 , 57 ]—the longer the recognition sequence, the longer the minimal intron size.…”
Section: Resultsmentioning
confidence: 99%
“…Pre-mRNA splicing is a crucial process in eukaryotes and is catalyzed by a spliceosome complex comprising five small nuclear ribonucleoproteins (snRNPs) and multiple non-snRNP-associated proteins [ 53 , 56 , 57 ]. Each snRNP comprises one or two snRNAs, a set of common Sm proteins, and a variable number of particle-specific proteins [ 53 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each snRNP comprises one or two snRNAs, a set of common Sm proteins, and a variable number of particle-specific proteins [ 53 , 58 ]. Recently, Nuadthaisong et al (2022) identified the presence of all snRNAs and conserved protein components of the spliceosome in Stentor , suggesting that conserved pre-mRNA splicing processes and mechanisms in eukaryotes exist in Stentor [ 56 ]. Similarly, in the present study, we found the presence of all snRNAs and most protein components of the spliceosome in P. cristata and O. trifallax .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation